The Implementation of a Project-Based Learning Jobsheet in Teaching Electrical Systems of Light Vehicle Bodies - Afindala, Ajib; Anis, Samsudin; Kusumawardani, Rini (Universitas Negeri Semarang, 2025)
One of the challenges faced in the recent learning process is that students have low psychomotor competency in learning job sheets related to the electrical systems of light vehicle bodies, such as in the lighting system, power window, sign lamp system, mirror cleaning system, and AC system. The use of unengaging job sheets led to low learning motivation and a decline in students’ psychomotor competencies. This study aimed to investigate the impact of a project-based learning job sheet on enhancing the psychomotor competencies of vocational students in the electrical systems of light vehicle bodies, including components such as the lighting system, power windows, signal lamp system, mirror cleaning system, and air conditioning system. This job sheet incorporated an innovative approach by integrating interactive visuals via QR codes, providing tutorial simulations of electrical systems in light vehicle bodies. This job sheet assisted students in understanding the material while encouraging active participation, collaboration, and high learning motivation. The present study employed research and development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subject of this study is XI grade students of Light Vehicle Engineering at Vocational (SMK) Gardua Nusantara Karanggawen with applied quantitative approach. The data collection technique used a pre-test and a post-test, with the results analyzed using linear regression through the SPSS application. The validation result of the media and material experts showed that the developed job sheet is very feasible with an average score of 4.83 (scale of 5). The practicality test carried out by the teacher achieved 86.55%, or it was declared as very practical. The jobsheet effectivity was proven through N-Gain significant score in the experimental class, which gained 76.94%, while the control class achieved 26.70%. In conclusion, the project-based learning job sheet is effective in enhancing students’ psychomotor competencies and has become a feasible medium for instruction.